Chemically derived Zn0.90-xMn0.05Fe0.05AlxO thin films: Tuning of crystallite/grain size, optical and dielectric constants and ferromagnetic properties through Al substitutions. (September 2018) - Babur, Y.; Tumbul, A.; Yıldırım, M.
Abstract: In this study, the role of Al substitution levels (x = 0.0–0.05) on the structure, surface morphology, optical constants, dielectric, electrical and magnetic properties of chemically derived Zn0.90-x Mn0.05 Fe0.05 Alx O (ZMFO:Alx ) thin films were systematically investigated. The results demonstrated the incorporation of Mn 2+, Fe 2+ and Al 3+ within ZnO wurtzite structure without any secondary phases. The crystalline quality of thin films was decreased systematically until x = 0.01 and then increased again for x = 0.03 and 0.05 Al substitution levels. Surface morphology analysis indicated homogeneous and smooth surface with spherical grains indicated the same trend with the crystalline quality in size upon on the Mn 2+, Fe 2+ and Al 3+ substitution levels. The confirmation of the Mn 2+, Fe 2+ and Al 3+ ions incorporated in ZnO host structure was successfully observed via XPS analysis. Optical analyses confirmed the blue shift of the band edge depended on the substitution of Mn 2+, Fe 2+ and Al 3+ within the ZnO crystal. Comparatively, the higher refractive index, extinction coefficient and dielectric constants were obtained for the ZMFO: Alx thin films than those of ZnO, Zn0.95 Mn0.05 O (ZMO) and Zn0.90 Mn0.05 Fe0.05 O (ZMFO) thin films. Hall measurements showed that all the film samples have n-type conductivity and it varies according to the crystallite size/grain sizes. Magnetic measurements showed higher room temperature ferromagnetic response for the ZMFO: Alx thin films than those of ZMO and ZMFO thin films due to having different oxygen vacancy concentrations. The highest room temperature was found for the Al substitution level of x = 0.03 thin film.